2022
DOI: 10.5935/1518-0557.20220035
|View full text |Cite
|
Sign up to set email alerts
|

Dual trigger vs. Conventional trigger outcomes in In Vitro Fertilization. Systematic review and meta-analysis

Abstract: Objective:The aim of this study is to analyze the efficacy of the dual trigger (human chorionic gonadotropin (hCG) + GnRH agonists) compared to the conventional trigger (hCG) in terms of oocyte retrieval (number and oocyte maturity), fertilization rate or number of embryos with two pronuclei, number of high-quality embryos, number of transferred embryos, number of cryopreserved embryos, implantation rate, positive β-hCG rate, ongoing pregnancy rate, abortion rate, and live birth rate.Methods: This search perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Dual trigger is a strategy initially used as rescue treatment to improve implantation rates and the overall reproductive outcomes in IVF patients who received GnRH-a alone for ovulation triggering [ 72 , 73 , 74 ]. However, the co-administration of the hCG to GnRH-a trigger increases OHSS risk [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dual trigger is a strategy initially used as rescue treatment to improve implantation rates and the overall reproductive outcomes in IVF patients who received GnRH-a alone for ovulation triggering [ 72 , 73 , 74 ]. However, the co-administration of the hCG to GnRH-a trigger increases OHSS risk [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, there was a notable increase in the quantity of mature oocytes and highquality embryos. According to a recent meta-analysis conducted by Gonzalez, it was found that the dual trigger group exhibited significantly higher rates of retrieved oocytes and clinical pregnancy when compared to other groups [26].…”
Section: Discussionmentioning
confidence: 99%
“…However a larger study is essential with regards to evaluation of embryo production as well as LBR results [16]. Gonzalez-Gonzalez V., et al [18]…”
Section: Discussionmentioning
confidence: 99%